2021
DOI: 10.1002/ejhf.2163
|View full text |Cite
|
Sign up to set email alerts
|

Virtual optimization of guideline‐directed medical therapy in hospitalized patients with heart failure with reduced ejection fraction: the IMPLEMENT‐HF pilot study

Abstract: Implementation of guideline-directed medical therapy (GDMT) for heart failure with reduced ejection fraction (HFrEF) remains incomplete. Non-cardiovascular hospitalization may present opportunities for GDMT optimization. We assessed the efficacy and durability of a virtual, multidisciplinary 'GDMT Team' on medical therapy prescription for HFrEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 30 publications
(34 reference statements)
3
44
0
Order By: Relevance
“…use of potassium binders for preventing hyperkalaemia leading to discontinuation of GDMT). [54][55][56][57]…”
Section: Frequent Discontinuation Of Guideline-directed Medical Thera...mentioning
confidence: 99%
“…use of potassium binders for preventing hyperkalaemia leading to discontinuation of GDMT). [54][55][56][57]…”
Section: Frequent Discontinuation Of Guideline-directed Medical Thera...mentioning
confidence: 99%
“…Bhatt et al 20 showed the usefulness of a pharmacist-physician GDMT team, compared to no team, to optimize treatment during a non-CV hospitalization of patients with HFrEF.…”
Section: Splanchnic Nerve Modulationmentioning
confidence: 99%
“…The study concluded that a structured remote patient management system reduced the percentage of days lost due to unplanned cardiovascular hospital admissions and all-cause mortality. 3 The innovative prospective, pre-post pilot interventional study by Bhatt et al, 4 represented by the acronym IMPLEMENT-HF, recruited 118 hospitalized patients to either usual care (n = 29) or a guideline-directed medical therapy (GDMT) Team intervention (n = 89), according to the month the patient was admitted. Criteria for exclusion were de novo HFrEF, recent acute coronary syndrome or stroke, recent cardiac surgery, systolic blood pressure <90 mmHg within the past 24 h, or coronavirus 2.…”
mentioning
confidence: 99%
“…The study by Bhatt et al, 4 aimed to address the inequality of treatment provision to HF patients managed on a general medical ward, following a non-cardiovascular admission. This was accomplished through a shared care model, with development and implementation of a pharmaceutical guideline-based protocol, provision of education to non-HF specialists, coordination of care and delineation of roles between physician, GDMT Team and cardiology team for future follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation